Challenges for mathematics teacher preparation in the third decade of this century (Innovaciones Educativas, 2021)
This work raises the urgency for transforming the training programs for teachers who teach Mathematics in Costa Rica. In order to support this contention, the situation of the Costa Rican Mathematics Reformation that began in 2012 is analyzed. National curricula from the second half of the 20th century are emphasized, and in particular, those of years 1964 and 1995 are pointed out. Firstly, we consider curricula dominated by the Reform of Modern Mathematics New Math), and secondly, programs that were formally declared “constructivist.” It is stated that in 2012 a final “coup de grace” was given to the New Math but, in addition, along with a break with behaviorism and other educational “paradigms” in convergence with research and experience in international Mathematics Education. The national educational crisis since 2020 has rethought conditions and rhythms for the Mathematics Reform, in particular, due to the serious decline in schooling. Here is where an adjustment in initial teacher training is needed.
Keywords: teacher preparation; mathematics; curriculum; Mathematics reform; Costa Rica; education